2021
DOI: 10.1111/cei.13650
|View full text |Cite
|
Sign up to set email alerts
|

Reduced infiltration of regulatory T cells in tumours from mice fed daily with gamma-tocotrienol supplementation

Abstract: Gamma‐tocotrienol (γT3) is an analogue of vitamin E with beneficial effects on the immune system, including immune‐modulatory properties. This study reports the immune‐modulatory effects of daily supplementation of γT3 on host T helper (Th) and T regulatory cell (Treg) populations in a syngeneic mouse model of breast cancer. Female BALB/c mice were fed with either γT3 or vehicle (soy oil) for 2 weeks via oral gavage before they were inoculated with syngeneic 4T1 mouse mammary cancer cells (4T1 cells). Suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In another study, γT3 supplementation caused marked inhibition tumour growth in prostate cancer ( Yap et al, 2010 ) and gastric cancer ( Manu et al, 2012 ). In our recent paper, we provided evidence that showed daily supplementation with γT3 modulated host immune response in this same syngeneic mouse model of breast cancer ( Subramaniam et al, 2021 ). Daily supplementation with γT3 reduced infiltration of Treg into the tumours, which correlate with decreased tumour growth and metastasis as well as regulated gene expression that supported Th1 responses.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In another study, γT3 supplementation caused marked inhibition tumour growth in prostate cancer ( Yap et al, 2010 ) and gastric cancer ( Manu et al, 2012 ). In our recent paper, we provided evidence that showed daily supplementation with γT3 modulated host immune response in this same syngeneic mouse model of breast cancer ( Subramaniam et al, 2021 ). Daily supplementation with γT3 reduced infiltration of Treg into the tumours, which correlate with decreased tumour growth and metastasis as well as regulated gene expression that supported Th1 responses.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies using cell-based and animal models have shown that T3 possess anti-cancer effects through various mechanisms ( Abraham et al, 2019 ; Montagnani Marelli et al, 2019 ). We have previously reported that tocotrienols possess anticancer ( Loganathan et al, 2021 ; Ramdas et al, 2019 , Ramdas et al, 2020 ), and immunomodulatory ( Subramaiam et al, 2021 ; Radhakrishnan et al, 2013 ) effects in cell-based and animal models. In addition, we also found that daily supplementation of palm vitamin E generated tumour-specific cytotoxic T-lymphocytes (CTL) in a syngeneic mouse model of breast cancer (BC) ( Hafid et al, 2013 ) as well as augmented immune response to tetanus toxoid vaccine ( Radhakrishnan et al, 2013 ; Mahalingam et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, γ-tocotrienol has been shown to raise circulating CD4+/CD8+ T-cells and natural killer cells, but to suppress regulatory T-cells in mice with mammary cancer. CD4+ T-cells were found to have infiltrated the tumors of γ-tocotrienol-fed mice [ 75 ]. These studies have shown that the immuno-modulatory effects of γ-tocotrienol could be dependent on disease status.…”
Section: Discussionmentioning
confidence: 99%
“…Tocotrienols have been shown to harbor anti-tumor activity, enhance gemcitabine activity, and d-tocotrienols have been shown to suppress NF-κB activation in pancreatic cancer. Experimental studies have also shown a reduction of the T regulatory cells infiltration in tumors by feeding mice with gamma-tocotrienol, 108 and intraperitoneal injections of alpha-tocopherol seem to abrogate the recruitment of MDSCs 109 . Thus, supplementation of, a-tocopherol and d-tocotrienol as soon as the diagnosis PDAC is made, should be considered, also because low side effects are expected 68,110 .…”
Section: Discussionmentioning
confidence: 99%